THE ABILITY TO HANDLE STRESS AS PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM (EDUCATION IN THE 21ST CENTURY, 2023)
Scientific achievements of researchers, who have studied the problem of ability to handlestress in various fields, which made it possible to set definitions, are analyzed in the article: stress– as a special reaction of the body to extrinsic stimuli; the ability to handle stress – as a personalcharacteristic of resistance to negative factors; and the key definition is withdrawn – theprofessional pilots ability to handle stress – the personal characteristic which gives the aviationspecialist an ability to adapt and be emotionally stable under the influence of stressors andmaintain high efficiency during working practice.It is pointed out that different types of occupational stress, such as informational, emotionaland communicative stress have been differentiated. As for the professional activity of aviationspecialists, the following negative factors are singled out: high neurotic-emotional tension; unusualspatial orientation; imposed work speed and lack of time; the presence of unusual professionalconditions of activity, which include such as noise, aircraft chatter vibration and acceleration stateduring performing various maneuvers; the advantage of brain work and almost complete absenceof physical effort, the presence of hypomobility and physical inactivation, etc.228The specific of the work of pilots lies in the special conditions of activity. In different modesof the technological process, the pilot performs his functions in the system, where control iscarried out by automatic air navigation systems. The specific of the work of pilots is determined ina number of ways: 1) high speed of technological process development; 2) processing largeamounts of information in a short period of time; 3) the sense of responsibility and the cost of errorin working practice; 4) the rapid transition from waiting period to strenuous work; 5) the intensityof work; 6) the rapid change of meteorological conditions; 7) negotiation monotonous noisefactors; 8) the constancy of visual images while observing a cloudy sky, flying in complex ones.Summing up what has been said, aviation workers belong to the category of people with ahigh level of occupational stress. There are main indicators of psychological readiness to performprofessional tasks under stress such as adaptive abilities to stress, professional reliability and theability to handle stress. Therefore, the formed ability to handle stress ensures the successfulperformance of professional duties, maintains high efficiency during the action of stress factors,which is an important condition for the professional activity of aviation professionals. In contrast,undeveloped ability to handle stress is characterized by an inability to perform professional dutiesin extreme situations, which can lead to both health problems and negative consequences inprofessional occupation.
Keywords: stress, professional stress, stress resistance, stress factor, civil aviation, pilot, professional activity